Model Komunikasi Kegiatan Remote Working - Rahma Yulia; Veranus Sidharta (Universitas Majalengka, 2023)
This research aims to describe the communication model used in remote working activities with a case study of PT employees. Riliv Indonesian Psychology. The research method used is descriptive qualitative using West & Turner's communication model theory. Data was collected through observation, structured interviews and documentation. The informants in this research were Human Capital, Partnership Manager, Product Operation, Social Media Manager, Creative Designer, and Senior Copywriter. The research results show that the communication model that occurs is an interactional communication model, where the communication process requires the sender and recipient of the message to both provide feedback. The interactional communication model is also used in new media so that it is in line with remote working activities which rely on communication technology in their activities. The type of communication in this activity is Computer Mediated Communication (CMC), where interaction occurs via a computer or internet as a medium for writing, sending, receiving and reading messages, either directly or indirectly. Communication process for work activities at PT. Riliv Psychology Indonesia uses three applications, namely Telegram, Google Meet, and Notion.